Max Weber diante do Socialismo - Carvalho, Davi Gustavo de [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
This work aims to analyse Max Weber's perspective in relation to the socialism. This great classic of the social thought argued against the feasibility of the socialist project from a very critical point of view. More precisely, this work delineates and analyses the double biased Weberian criticism towards socialism: Weber not only opposes the idea that the human emancipation would be reached in an established socialist society, but also criticises the possibilities of success of a social revolution that could lead to that sort of society. Unveiled the arguments that underpin Weber's criticism, the subsequent critical discussion of the author's reasons is addressed in the light of the historical background in which the German thinker has come up with them. The chain of values that guided the author, which provides the basis for his political-ideological position, seems to exert great influence on the view he holds on socialism, which he has only seen as an extensive form of the bureaucratic domination, something that has already existed in its predecessor, the modern capitalism. Taking that very idea as pivotal, that negative view of socialism, Weber has considered there was no way out for the cage of iron of bureaucracy, thus claiming it was something inexorable in modern times, either in capitalism or in socialism, capitalism's supposed antipodal. Finally, even though some historical developments of the socialist experiences give reason to Weber's arguing, the Weberian theorisation and his arguing, whose strength and influence are undeniable, are questioned here based on some critical elements. In order to do so, a wide range of Weber's works are browsed and analysed; the famous Conference on Socialism, though, proffered by Weber in 1918, is here taken as the fundamental document for research

Este trabalho tem como objeto de análise a perspectiva de Max Weber em relação ao socialismo. Esse grande clássico do pensamento social sustentou posição muito crítica em relação à exequibilidade do projeto socialista. Mais precisamente, este trabalho delineia e analisa a crítica weberiana ao socialismo em sua dupla abrangência: Weber contrapõe-se tanto à ideia de que a emancipação humana seria atingida em uma sociedade socialista estabelecida, quanto às próprias possibilidades de êxito de uma revolução social que caminhasse no sentido da construção dessa sociedade. Inicialmente revelados os argumentos weberianos que sustentam tal postura, passa-se à sua subsequente discussão crítica à luz do contexto histórico na qual o pensador alemão os forjou. A cadeia de valores que norteavam o autor - base de sua postura político-ideológica - parece influenciar sobremaneira seu ponto de vista sobre o modo de produção socialista, o qual via apenas como extensão radicalizada da dominação burocrática, algo já existente em seu predecessor, o capitalismo moderno. Tomando precisamente essa ideia como central, não vislumbrava saída para a jaula de ferro da burocracia, apresentando-a como algo inexorável na modernidade, seja no capitalismo, seja no seu suposto antípoda, o socialismo. Por fim, muito embora desdobramentos históricos das experiências socialistas tenham dado razão a Weber, apresentam-se alguns elementos críticos à elaboração teórica weberiana, problematizando-se alguns aspectos de sua argumentação, cuja força e influência são inegáveis. Para isso, textos variados de sua obra são percorridos e analisados, embora tome como documento central a célebre Conferência sobre o Socialismo, proferida por Weber em 1918
Keywords: Weber, Max 1864-1920; Socialismo; Capitalismo; Burocracia; Ideologia; Ideology